Divided governmental structure and state compliance with international human rights law: A reputation-based approach. (31st May 2021) - Nie, Mintao
Abstract: Previous research has analysed a range of domestic stakeholders that make national governments' commitments to international human rights law credible, including an independent judiciary, legislative veto players, political opposition groups, and non-governmental organizations. But how do the power dynamics within the government affect state compliance with international human rights law? Building on the basic understanding that international human rights law needs to pass through domestic political and administrative processes before it can be implemented on the ground, this article articulates a reputation-based theoretical framework to explain how the lack of reputational mechanisms at the local level and national leaders' shifting of blame for non-compliance to sub-national officials and the internal governance structure – two salient characteristics in a decentralized political system – make international human rights law less effective. A case study of US compliance with Article 36 of the 1963 Vienna Convention on Consular Relations sheds light on how international reputational concerns interact with divided authority structure to shape national leaders' and subnational authorities' policy responses to the enforcement of international human rights standards.